Implementation of the Gerbang Biru Ciliwung Program as an Innovation Framework for Waste Management Based on Environmental Education at SMPN 34 Depok - Wendi Gustira; Devy Puspasari Siswaningrum; Nur Rahmi F. Yanti; Fanny Shinta (Prospect Publishing, 2026)
The issue of organic waste in urban areas, particularly along the banks of the Ciliwung River, has become increasingly complex due to high community activity and limited access to sustainable waste management innovations. The CSR program GERBANG BIRU CILIWUNG, initiated by PT Perusahaan Gas Negara Tbk through Offtake Stasiun Cimanggis, in collaboration with SMPN 34 Kota Depok, academics, and local communities, introduced a community empowerment-based social innovation through the utilization of biodigesters and the educational media Pelita Ciliwung Book. This study employed a participatory approach involving communities and schools in organic waste management and environmental education. The findings indicate that the biodigester reduced organic waste accumulation while simultaneously producing biogas as an alternative energy source for the school canteen. Furthermore, the Pelita Ciliwung Book effectively enhanced students’ understanding, environmental awareness, and participation in environmental management practices. The collaboration among corporations, academics, schools, and communities demonstrates that environmental education-based social innovation can serve as a sustainable strategy for addressing organic waste problems in urban areas.